ANALYSIS OF VERBAL MATHEMATICAL COMMUNICATION IN OPEN-ENDED PROBLEM SOLVING - Indri Susilowati; Yus Mochamad Cholily; Alfiani Athma Putri Rosyadi; Akhsanul In'am (Jurnal Tunas Pendidikan, 2025)
The ability to communicate mathematical ideas orally is crucial for studying mathematics. One way to measure oral communication skills is by presenting an open-ended problem to students. This study aims to illustrate how students solve open-ended issues using oral mathematical communication skills. The methodology is a qualitative descriptive study; the subject of the research is grade VIII junior high school students with low, medium, and high levels of mathematical ability to communicate when working on open-ended problems. From this study, students who have a low level of communication ability have not met all the indicators optimally, because the understanding of symbols and their use is still weak. Students in the medium level that satisfy the markers of mathematical communication, because the notation used is appropriate and consistent and students can provide concise, clear, and thorough explanations. Students with high categories meet all indicators very well, because they are able to use complete and accurate mathematical symbol and students can provide concise, clear, and reflective explanations. Students in lower categories' have not fully satisfied all of the requirements for mathematical communication. The medium-level pupils satisfy the requirements for mathematical communication. Students with high categories meet all mathematical communication indicators very well.